Phase‐Changing Microcapsules Incorporated with Black Phosphorus for Efficient Solar Energy Storage - Huang, Hao (Adv Sci (Weinh), 2020)
A new solar energy storage system is designed and synthesized based on phase‐changing microcapsules incorporated with black phosphorus sheets (BPs). BPs are 2D materials with broad light absorption and high photothermal performance, which are synthesized and covalently modified with poly(methyl methacrylate) (PMMA) to produce the PMMA‐modified BPs (mBPs). With the aid of PMMA, the mBPs and phase‐changing materials (PCM, eicosane) are encapsulated together to form microcapsules. The microencapsulated eicosane and mBPs (mBPs‐MPCM) composites exhibit a high latent heat of over 180 kJ kg(−1), good thermal reliability, as well as excellent photothermal characteristics inherited from BPs. Owing to the direct contact in the integrated mBPs‐MPCM composites, the thermal energy generated by mBPs is transferred to eicosane immediately giving rise to three times higher efficiency in solar energy storage compared to microcapsules with mBPs on the surface. The mBPs‐MPCM composites have great potential in solar energy storage applications and the concept of integrating photothermal materials and PCMs as the core provides insights into the design of high‐efficiency solar energy storage materials.